RESULTS OF TREATMENT OF EDENTULOUS PATIENTS WITH DENTURES MADE OF «FTORAX» - V.M. Dvornyk; H.M. Kuz; O.B. Tumakova; O.S. Shemetov; V.S. Kuz (Український стоматологічний альманах)
Background. The problem of providing high-quality dental care to edentulous patients remains one of the most important and unresolved to this day in the clinic of prosthodontics. The causes of complete loss of teeth can be both periodontal tissue diseases and diseases of hard tooth tissues of carious and non-carious origin, trauma and the like. It becomes necessary to fabricate complete removable dentures to prevent the occurrence of pathologies in such situations. Complete secondary adentia leads to a large number of local and general complications. The chewing apparatus undergoes a number of functional and morphological changes. Therefore, the complete absence of teeth sets the dentist the task of restoring the functions of full chewing, the appearance of the patient, and speech. The complexity of high-quality prosthetics for edentulous patients is also because the clinical characteristics of supporting tissues are diverse, constantly changing, so a personal approach to creating stable denture is needed. It should be added that the fabrication of high-quality complete removable dentures largely depends on the properties of the base material. The main group of materials for the fabrication of such dentures is acrylic plastics.